A 0.6-µW Chopper Amplifier Using a Noise-Efficient DC Servo Loop and Squeezed-Inverter Stage for Power-Efficient Biopotential Sensing - Xuan Thanh Pham; Ngoc Tan Nguyen; Van Truong Nguyen; Jong-Wook Lee (Sensors, 2020)
To realize an ultra-low-power and low-noise instrumentation amplifier (IA) for neural and biopotential signal sensing, we investigate two design techniques. The first technique uses a noise-efficient DC servo loop (DSL), which has been shown to be a high noise contributor. The proposed approach offers several advantages: (i) both the electrode offset and the input offset are rejected, (ii) a large capacitor is not needed in the DSL, (iii) by removing the charge dividing effect, the input-referred noise (IRN) is reduced, (iv) the noise from the DSL is further reduced by the gain of the first stage and by the transconductance ratio, and (v) the proposed DSL allows interfacing with a squeezed-inverter (SQI) stage. The proposed technique reduces the noise from the DSL to 12.5% of the overall noise. The second technique is to optimize noise performance using an SQI stage. Because the SQI stage is biased at a saturation limit of 2VDSAT, the bias current can be increased to reduce noise while maintaining low power consumption. The challenge of handling the mismatch in the SQI stage is addressed using a shared common-mode feedback (CMFB) loop, which achieves a common-mode rejection ratio (CMRR) of 105 dB. Using the proposed technique, a capacitively-coupled chopper instrumentation amplifier (CCIA) was fabricated using a 0.18-µm CMOS process. The measured result of the CCIA shows a relatively low noise density of 88 nV/rtHz and an integrated noise of 1.5 µVrms. These results correspond to a favorable noise efficiency factor (NEF) of 5.9 and a power efficiency factor (PEF) of 11.4.